Development of a chemically disclosed serum-free medium for mouse pluripotent stem cells - Katayama, Tomoka; Takechi, Marina; Murata, Yamato; Chigi, Yuta; Yamaguchi, Shinpei; Okamura, Daiji (Frontiers in Bioengineering and Biotechnology, 2024)
Mouse embryonic stem cells (mESCs) have been widely used as a model system to study the basic biology of pluripotency and to develop cell-based therapies. Traditionally, mESCs have been cultured in a medium supplemented with fetal bovine serum (FBS). However, serum with its inconsistent chemical composition has been problematic for reproducibility and for studying the role of specific components. While some serum-free media have been reported, these media contain commercial additives whose detailed components have not been disclosed. Recently, we developed a serum-free medium, DA-X medium, which can maintain a wide variety of adherent cancer lines. In this study, we modified the DA-X medium and established a novel serum-free condition for both naïve mESCs in which all components are chemically defined and disclosed (DA-X-modified medium for robust growth of pluripotent stem cells: DARP medium). The DARP medium fully supports the normal transcriptome and differentiation potential in teratoma and the establishment of mESCs from blastocysts that retain the developmental potential in all three germ layers, including germ cells in chimeric embryos. Utility of chemically defined DA-X medium for primed mouse epiblast stem cells (mEpiSCs) revealed that an optimal amount of cholesterol is required for the robust growth of naïve-state mESCs, but is dispensable for the maintenance of primed-state mEpiSCs. Thus, this study provides reliable and reproducible culture methods to investigate the role of specific components regulating self-renewal and pluripotency in a wide range of pluripotent states.